2009
DOI: 10.1007/s00264-009-0845-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of platelet-rich plasma for the treatment of refractory jumper’s knee

Abstract: The aim of this study was to evaluate the efficacy of multiple platelet-rich plasma (PRP) injections on the healing of chronic refractory patellar tendinopathy after previous classical treatments have failed. We treated 15 patients affected by chronic jumper's knee, who had failed previous nonsurgical or surgical treatments, with multiple PRP injections and physiotherapy. We also compared the clinical outcome with a homogeneous group of 16 patients primarily treated exclusively with the physiotherapy approach.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
212
1
17

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 285 publications
(235 citation statements)
references
References 24 publications
5
212
1
17
Order By: Relevance
“…Some studies of PRP administration in tendinopathy have demonstrated the validity of such a therapeutic option in cases which were unresponsive to conservative therapy alone [36,38]. However, other studies of large series have reported that PRP treatment of tendinopathy is no more effective than placebo [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of PRP administration in tendinopathy have demonstrated the validity of such a therapeutic option in cases which were unresponsive to conservative therapy alone [36,38]. However, other studies of large series have reported that PRP treatment of tendinopathy is no more effective than placebo [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The delivery of bone marrow mononucleated cells (BMMNCs) has been described as an alternative procedure to grafting MSCs in injured tissues, and preclinical studies have shown promising results for the treatment of tendinopathy [10,11]. Analogous animal models have also suggested the usefulness of platelet concentrate for the treatment of tendon damage, leading to the application of PRP in humans, where the first reports seem to confirm the potential of PRP to increase the tissue healing potential [12,13]. However, both treatment approaches raise controversies, due to the lack of scientifically robust studies demonstrating their effectiveness unequivocally, contradictory results in some therapeutic applications, and to the only partial clinical efficacy of these biological regenerative methods documented in other studies [4,14].…”
Section: Introductionmentioning
confidence: 99%
“…13,29 However, the role of PRP in other tendinopathies like Achilles tendinopathy has not been encouraging, 30,31 despite successful usage of PRP in patellar tendinopathies. 32,33 Plantar fasciitis is also another commonly encountered problem which at times can be frustrating to both the patient and the treating doctor. Our experience with PRP has again shown consistently good results, with support from various studies; however, we recommend that this option should be kept for recalcitrant cases 34 that fail all conventional modalities.…”
Section: Discussionmentioning
confidence: 99%